The effect of ethnicity and social deprivation on outcomes after resuscitated out-of-hospital cardiac arrest. (3rd May 2023) - Roy, R; Kanyal, R; Abd Razak, M; To-Dang, B; Chotai, S; Abu-Own, H; Cannata, A; Dworakowski, R; Webb, I; Pareek, M; Shah, A M; Maccarthy, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): This work was part funded by King's College Hospital R&D Grant and was supported by the Department of Health via a National Institute for Health Research Biomedical Research Centre award to Guy's & St Thomas' NHS Foundation Trust in partnership with King's College London and King's College Hospital NHS Foundation Trust. Background: Out-of-hospital cardiac arrest (OOHCA) is a common cause of morbidity and mortality. There is substantial ethnic variation in OOHCA outcomes, though it is unclear if these discrepancies are due to arrest circumstances or socioeconomic and biological factors. Purpose: To investigate the association of ethnicity, social deprivation and co-morbidities with rates of coronary artery disease, subsequent treatment and outcome in resuscitated OOHCA patients with primary cardiac aetiology. Methods: 526 patients with resuscitated OOHCA of suspected cardiac aetiology were included in the study registry between 1-May-2012 and 31-December-2020. Ethnicity, social deprivation, arrest circumstances, comorbidities and extent of coronary artery disease (CAD) were measured. The primary endpoint was 12-month mortality. Results: Of 526 patients (median age 62.0±21.1, 74.1% male), 78.1% had shockable rhythms, 83.6% were witnessed and 77.6% had bystander cardiopulmonary resuscitation (CPR). 414 patients (78.7%) were White, 35 (6.7%) were Asian, and 77 (14.6%) were Black. Black patients had more co-existent hypertension and cardiomyopathy, but less prior coronary revascularisation compared with White/Asian patients. There were no ethnic differences in location, witnesses, or bystander CPR, but Black patients had more non-shockable rhythms. Admission serum lactate and creatinine levels were higher in Black patients, but troponin levels were lower than in White/Asian patients. Black patients received less immediate coronary angiography (CAG) and percutaneous coronary intervention (PCI), but had lower rates of CAD, with less CAD complexity (lower SYNTAX and Jeopardy scores) than White/Asian patients. Mortality at 12 months was highest amongst Black followed by Asian and then White patients. In Black patients, this excess mortality was driven by higher rates of multi-organ dysfunction but lower cardiac death than White, and in particular Asian patients, amongst whom cardiac death was highest. Stratifying patients by socioeconomic status showed that higher social deprivation was associated with non-shockable and unwitnessed OOHCA but other demographics, arrest circumstances, rates of CAG and PCI were similar and no difference in mortality or cause of death at 12 months was observed. In a multi-variable logistic regression analysis, age, location of OOHCA, witnessed arrest and Black compared to White ethnicity were independent predictors of 12-month mortality, whilst social deprivation was not. Conclusion: Black patients have higher mortality after resuscitated OOHCA than White patients due to differing underlying aetiology rather than differences in arrest circumstances or social deprivation. This should be reflected in cardiac arrest pathways, and patients conveyed to cardiac arrest centres should have access to coronary angiography but also advanced 24/7 imaging, renal replacement therapy and other advanced critical care therapies. Baseline demographics and outcomes